2006
DOI: 10.1038/nm1457
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of antibody responses against multiple antigens of the two infectious forms of Vaccinia virus provides a benchmark for smallpox vaccination

Abstract: Smallpox was eradicated without an adequate understanding of how vaccination induced protection. In response to possible bioterrorism with smallpox, the UK government vaccinated approximately 300 health care workers with vaccinia virus (VACV) strain Lister. Antibody responses were analyzed using ELISA for multiple surface antigens of the extracellular enveloped virus (EEV) and the intracellular mature virus (IMV), plaque reduction neutralization and a fluorescence-based flow cytometric neutralization assay. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
154
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(171 citation statements)
references
References 28 publications
14
154
1
2
Order By: Relevance
“…Under nonreducing conditions, D8L⌬-GST appears as a monomer, A27L-GST as trimers, and B5R⌬-GST as oligomers (data not shown). It was also of interest to determine whether the E. coli-expressed vaccinia virus proteins can be recognized by human immune serum, since antibody responses to A27L, D8L, and B5R are induced in humans after immunization with live smallpox vaccine (8,36). Western blot analysis showed that the A27L, D8L, and B5R proteins expressed in E. coli did not react with human preimmune serum but were reactive with human serum collected 4 weeks after vaccination with Dryvax (data not shown).…”
Section: Immunization Of Mice With E Coli-expressed A27l D8l⌬ and mentioning
confidence: 99%
See 1 more Smart Citation
“…Under nonreducing conditions, D8L⌬-GST appears as a monomer, A27L-GST as trimers, and B5R⌬-GST as oligomers (data not shown). It was also of interest to determine whether the E. coli-expressed vaccinia virus proteins can be recognized by human immune serum, since antibody responses to A27L, D8L, and B5R are induced in humans after immunization with live smallpox vaccine (8,36). Western blot analysis showed that the A27L, D8L, and B5R proteins expressed in E. coli did not react with human preimmune serum but were reactive with human serum collected 4 weeks after vaccination with Dryvax (data not shown).…”
Section: Immunization Of Mice With E Coli-expressed A27l D8l⌬ and mentioning
confidence: 99%
“…The importance of including A27L, D8L, and B5R as components of a subunit smallpox vaccine is underscored by the detection of antibody responses to both IMV-and EEV-associated proteins in the sera of humans immunized with Dryvax (25) or vaccinia virus strain Lister (36). Studies with nonhuman primates or mice have also demonstrated that immunization with baculovirus-expressed recombinant proteins or DNA vaccines composed of different combinations of IMV-and EEVassociated proteins-such as A33R, B5R, and L1R (14,15), A27L, A33R, L1R, and B5R (21), or A27L, B5R, L1R, A33R, and D8L (41)-result in the induction of high levels of neutralizing antibodies and in the protection of mice from lethal challenge with vaccinia virus.…”
mentioning
confidence: 99%
“…In contrast, extracellular enveloped virions (EEV) have double membranes and are formed by the extrusion of virions through the cell surface membrane, and they are thought to be important for virus propagation within the host (21,24,26). Vaccinia virus (Dryvax) vaccination has been shown to induce neutralizing antibodies (NAbs) against membrane glycoproteins of both variants, including IMV antigens L1R and A27L and EEV antigens B5R and A33R (12,19,23).…”
mentioning
confidence: 99%
“…The B5R viral protein is the only immune-targeted viral protein exposed on the surface of the EEV (18), and although neutralizing antibodies against this protein are typically produced in an effective immunization, only a small percentage of the antibodies recognize B5R antigens (as the majority of the antibodies produced recognize the more antigenic intracellular virus version of the virus; ref. 19). It is therefore possible that an increased release of EEV into the blood stream will result in some evasion or ''swamping'' of this neutralizing antibody and systemic spread of the virus to distant tumors.…”
Section: Discussionmentioning
confidence: 99%